An exploratory study on the influencers of the perceived relevance of CIO's activities - Varajão, João (2016)
Over the past decades several studies aimed to rank the importance of CIO's activities. One aspect that stands out in these studies is the difficulty in finding two studies that agree on the relative importance of CIO's activities. On the one hand, this can be explained by the CIO role evolution. On the other hand, there may be certain variables that influence the perception of the importance of CIO's activities. This paper presents the results of an exploratory study developed to identify the current CIO's main activities and to verify whether CIO's demographics and CIO's business context influence the perception of the importance of those activities. The results show that managing projects, interacting with top management teams, optimizing business processes and making strategic decisions are main CIO's activities; and the importance recognized to these activities is influenced by characteristics such as the CIO's age or the hierarchical structure of the organization.